2007
DOI: 10.1007/s00500-006-0148-5
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo methods in fuzzy linear regression

Abstract: We apply our new fuzzy Monte Carlo method to a certain fuzzy linear regression problem to estimate the best solution. The best solution is a vector of triangular fuzzy numbers, for the fuzzy coefficients in the model, which minimizes one of two error measures. We use a quasi-random number generator to produce random sequences of these fuzzy vectors which uniformly fill the search space. We consider an example problem and show this Monte Carlo method obtains the best solution for one error measure and is approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Mehran et al (2005) reviewed relevant articles on fuzzy regression and provided a simple approach to determine the coefficients of a fuzzy linear relationship. Meanwhile, Abdalla and Buckley (2007) applied a new fuzzy Monte Carlo method to a certain fuzzy linear regression problem to estimate the best solution. In this case, the best solution is a vector of triangular fuzzy numbers for the fuzzy coefficients in the model, which minimises one of two error measures.…”
Section: Overview Of Related Workmentioning
confidence: 99%
“…Mehran et al (2005) reviewed relevant articles on fuzzy regression and provided a simple approach to determine the coefficients of a fuzzy linear relationship. Meanwhile, Abdalla and Buckley (2007) applied a new fuzzy Monte Carlo method to a certain fuzzy linear regression problem to estimate the best solution. In this case, the best solution is a vector of triangular fuzzy numbers for the fuzzy coefficients in the model, which minimises one of two error measures.…”
Section: Overview Of Related Workmentioning
confidence: 99%
“…Therefore, in order to obtain more information, the fuzzy relation among collected actual data in fuzzy regression was first introduced by Tanaka et al (1982). Many researches, for examples, Watada (1992) uses fuzzy regression to time series to analyze time series data; Chang (1997) showed that the fuzzy regression model could be better explained in seasonal analysis; Tsaur et al (2002) used two independent variables of preceding periodical data and index of time to show the pattern of the seasonal variation; Tsaur (2003) showed that the fuzzy regression model could be used to forecast the demand of internet users under different product life cycles; Abdalla and Buckley (2007) apply fuzzy Monte Carlo method to a certain fuzzy linear regression problem to estimate the best solution, and find that the best solution is a vector of triangular fuzzy numbers for the fuzzy coefficients in the model. Therefore, for analyzing limited time series data with the reliability and validity, the fuzzy set theory is hybridized into the grey model GM(1,1) to derive fuzzy grey model GM(1,1) (Tsaur and Liao 2007), fuzzy grey regression model (Tsaur 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A different fuzzy linear regression model was studied in Abdalla and Buckley (2007a). In Abdalla and Buckley (2007a) the independent variables were crisp (not fuzzy), the dependent variable was a triangular fuzzy number and the unknown coefficients were also triangular fuzzy numbers.…”
Section: Introductionmentioning
confidence: 99%
“…In Abdalla and Buckley (2007a) the independent variables were crisp (not fuzzy), the dependent variable was a triangular fuzzy number and the unknown coefficients were also triangular fuzzy numbers. In Abdalla and Buckley (2007a), we used the same two error measures (defined below), compared our results using fuzzy Monte Carlo to the results in four other publications and in all cases, except one, obtained smaller error. This one case where our Monte Carlo method did not produce the smallest error is similar to that discussed in Sect.…”
Section: Introductionmentioning
confidence: 99%